Reversible Data Hiding Algorithm in Encrypted Images with Difference Encoding and Block Compression - Guoqing GE; Bin GE; Chenxing XIA; Zhimeng WANG (工程科学与技术)
With the development of digital information and cloud-computing technology toward maturity, reversible hiding of data in encrypted images is gradually becoming an area of intensive research for protection of data privacy in communications. Nonetheless, notable challenges still exist regarding achieving greater compression of carriers to enhance embedding capacity by adaptive-recognition coding of pixels in local areas based on the distribution characteristics of pixels in different cover images. To address the problem of the low embedding capacity of reversible information hiding due to insufficient utilization of redundant space in carrier images, herein, a cipher-text domain-reversible data-hiding algorithm is proposed based on difference coding and block compression. First, the difference-image matrix is classified and adaptively coded according to the maximum difference value within the block based on the differences of strong-correlation neighbors in local areas of the natural image. At the same time, the original image is chunked, disrupting the order between blocks and diffusing pixels within blocks to ensure the security of the image information. Then, according to the result of the adaptive coding of the difference-pixel blocks, the redundant space is compressed on the corresponding encrypted image blocks, and the secret data is finally embedded by bit replacement. In contrast to previous algorithms , this approach rearranges the bits of the differential-encoded image, starting from the least-significant bit of the cipher-text image pixel, marking the sign bit of the differential pixel, and marking the least-significant differential bit in each of the remaining planes in turn. Due to the reversibility of the encryption operation and adaptive coding, a legitimate receiver can achieve lossless reconstruction of the original plain-text image and error-free extraction of the secret data. The experimental results show that the proposed algorithm has a greater embedding rate and better security than several existing algorithms. The average embedding rates were found to be 3.027 and 2.937 bpp for the BOSSbase and BOWS–2 datasets, respectively, and this was also improved by more than 0.57 bpp on classical test images.